Highly Efficient and Durable Pd Hydride Nanocubes Embedded in 2D Amorphous NiB Nanosheets for Oxygen Reduction Reaction. Issue 21 (21st July 2017) - Lu, Yizhong; Wang, Jiong; Peng, Yuecheng; Fisher, Adrian; Wang, Xin
Abstract: A highly efficient and durable electrocatalyst of Pd hydride nanocubes encapsulated within 2D amorphous Ni‐B nanosheets is reported. The PdH0.43 nanocubes are first synthesized via a simple N, N ‐dimethylformamide thermal treatment. The as‐synthesized PdH0.43 nanocubes are then encapsulated in 2D amorphous NiB nanosheets by NaBH4 reduction in the presence of nickel species. During the NaBH4 treatment, the PdH0.43 can be further transformed into PdH0.706 due to the presence of endogenous H2 . Electrochemical studies demonstrate that the degree of hydride of Pd nanocubes (PdH x ) plays an important role in the enhancement of their oxygen reduction reaction (ORR) activity. With increasing x value, both the activity and stability increase significantly. At 0.90 V versus reversible hydrogen electrode, the ORR activity of PdH0.706  @Ni‐B reaches 1.05 A mgPd −1, which is nearly five times higher than that of the state‐of‐the‐art Pt catalysts. Accelerated durability tests show that even after 10 000 potential cycles, there is negligible shift in their half‐wave potential and no shape and structure change occurs, indicating the incorporation of amorphous 2D Ni‐B nanosheets can greatly improve their stability without compromising their activity. The present study illustrates the importance of high degree of hydride and presence of amorphous Ni‐B nanosheets on the enhancement of ORR activity for Pd‐based electrocatalyst. Abstract : Highly efficient and durable PdH0.706  @Ni‐B electrocatalysts toward oxygen reduction reaction are obtained by simple N, N ‐dimethylformide hydrothermal treatment and subsequent 2D Ni‐B nanosheets encapsulation. Electrochemical studies show that the oxygen reduction reaction activity increases with increasing the x value in PdH x and the presence of amorphous Ni‐B nanosheets can significantly improve stability.